Present scenario of Fair Face Holdings Ltd. (In the Context of Real Estate Sector of BD) - Tanim, Sabit Rahman (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2015.